DESAIN PROTOTYPE APLIKASI “PEJUANG JLPT” SEBAGAI MEDIA PEMBELAJARAN BERBASIS METODE DELIBERATE PRACTICE - Bambang Roberto; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research is about the process of designing a prototype for the Dokkai learning application as a self-learning medium specifically for JLPT preparation. The application is named "Pejuang JLPT" (JLPT Warrior). The objective of this research is to analyze and design the interface design and user experience (User Interface/User Experience) in order to develop and use it as a self-learning medium specifically for mastering comprehension of the dokkai subject in JLPT. The method used in this research is design thinking. Data collection was carried out by distributing questionnaires to 20 respondents and conducting interviews with 5 individuals out of those 20 respondents.. The data analysis technique is described using qualitative descriptive data analysis. The analyzed data is then depicted as ideas and solutions for dokkai problems and the use of the application by the respondents. After ideation and solution depiction, interface design and prototyping are carried out. Finally, the prototype is tested and evaluated by expert validators in the field of media and content. The raw evaluation results are processed and calculated using the System Usability Scale (SUS), and good scores are obtained in terms of media and satisfactory scores in terms of content.Key Words: Prototype, Language Learning Media, Deliberate Practice